Esofagite eosinofílica em pacientes com paralisia cerebral - Nápolis, Ana Carolina Ramos de (2014)
Introduction: Cerebral palsy patients often have dysfunction of the gastrointestinal tract and eosinophilic esophagitis can be present. Objective: The aim of this study is to describe medical records of pediatric patients with cerebral palsy related to eosinophilic esophagitis. Methods: Cross-sectional, retrospective and descriptive study that evaluates the medical records data of pediatric patients with diagnosis of cerebral palsy and eosinophilic esophagitis in a tertiary center of Pediatric Gastroenterology between August 2005 and August 2013. Results: A hundred and thirty-one patients with cerebral palsy were followed in Ambulatório de Gastroenterologia Pediátrica da Universidade Federal de Uberlândia. Seven had eosinophilic esophagitis associated. The age ranged from 70 to 156 months with a mean average of 104.7 months. The age of detection of esophageal eosinophilia ranged from 23 to 112 months, with a mean of 52.3 months. Five of seven patients filled the criteria for eosinophilic esophagitis. Conclusion: Gastrointestinal disorders are the major chronic problem in most of children with cerebral palsy. The investigation of eosinophilic esophagitis should be done regularly in those patients, once this entity could overlap other gastrointestinal diseases.